Organizing, Contextualizing, and Storing Legacy Research Data: A Case Study of Data Management for Librarians. - Brianna Marshall; Katherine O'Bryan; Rebecca Vernon (Issues in Science and Technology Librarianship, 2013)
Librarians are increasingly expected to work with researchers to organize and store large amounts of data. In this case study, data management novices undertake responsibility for a legacy public health research dataset. The steps taken to understand and manage the legacy dataset are explained. As a result of the legacy dataset experience, the authors of this study identified three main issues to resolve during a data management project: file organization, contextualizing data, and storage and access platforms. Finally, recommendations are made to help librarians working with legacy data identify solutions to these problems. [ABSTRACT FROM AUTHOR]